Products of Innovative Thinking and Stages of Their Implementation (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examines the products of innovative thinking and their modern manifestations. It talks about the steps that need to be followed to implement innovative thinking.